Phosphaalkene-oxazoline copolymers with styrene as chiral ligands for rhodium(i). Issue 13 (29th February 2016) - Serin, Spencer C.; Dake, Gregory R.; Gates, Derek P.
Abstract : The radical-initiated copolymerization of phosphaalkene-oxazoline, MesPC(Ph)CMe2 Ox [1, Ox = CNOCH(iPr)CH2 ] with different loadings of styrene affords poly(methylenephosphine- co -styrene)s [2a (1  : S = 1 : 2): M w = 7400 g mol −1, PDI = 1.1;2b (1  : S = 1 : 5): M w = 18 000 g mol −1, PDI = 1.2;2c (1  : S = 1 : 10): M w = 16 000 g mol −1, PDI = 1.3]. Abstract : The radical-initiated copolymerization of phosphaalkene-oxazoline, MesPC(Ph)CMe2 Ox [1, Ox = CNOCH(iPr)CH2 ] with different loadings of styrene affords poly(methylenephosphine- co -styrene)s [2a (1  : S = 1 : 2): M w = 7400 g mol −1, PDI = 1.1;2b (1  : S = 1 : 5): M w = 18 000 g mol −1, PDI = 1.2;2c (1  : S = 1 : 10): M w = 16 000 g mol −1, PDI = 1.3]. Copolymers2a–2c are demonstrated as viable macromolecular ligands for rhodium(i ). By comparison with the crystallographically characterized model P, N-bidentate complex, [Mes(Me)P–CH(Ph)CMe2 Ox·Rh(cod)]BF4, the polymer complexes [2 ·Rh(cod)]BF4 were prepared. The macromolecular metal complexes were characterized by GPC {for [2a ·Rh(cod)]BF4 : M w = 14 000 g mol −1, PDI = 1.2}, UV/Vis spectroscopy, 1 H, 13 C and 31 P NMR spectroscopy. Integration of the 31 P NMR spectra of mixtures of2 and [Rh(cod)2 ]BF4 permitted the determination of the mol% of incorporation of monomer1 in copolymer2 (2a : 17%;2b : 5%;2c : 4%). These results compared favorably with those determined by elemental analysis (2a : 17%;2b : 6%).